Treatment of slaughterhouse wastewaters by anaerobic submerged membrane bioreactor - Aslan, Mustafa; Arı, Halil; Gülşen, Hakkı; Yıldız, Hakan; Saatçi, Yusuf (My University, 2013)
Anaerobic submerged membrane (SAnMBR) system in treatment the slaughterhouse industry wastewater has a high COD with a value around 4600 mg/l and mesophilic temperature (35 ± 2°C) value, which is put into the hallow fiber membrane module with a 1.5 liters reactor system were studied. Experimental values of COD, solids, alkalinity, VFA, TP, TN, and oil-grease parameters have been measured periodically. Results of the analysis were measured the output values of COD removal efficiency of 95% with a value around 400 mg/l. Alkalinity values were decreased from 1600-1800 (mg CaCO3/l) to 1000-1200 (mg CaCO3/l). The same way as the initial values of VFA 200-300 (HoAc/l) was found, and these values are a result of treatment 120-160 (HoAc/l) were measured. While the measured initial parameters of TN and TP were 300 mg/l and 45 mg/l, respectively, these values have decreased to 240 mg/l and 15 mg/l, respectively at the system output. Though oil-grease values for the other analyses of the initial water were observed around 1000 mg/l, decreased to 45 mg/l at about 90% efficiency. The results of the analyses show that all the established anaerobic submerged membrane (SAnMBR) system was operated with high efficiency for treated slaughterhouse industry wastewater.

Mezbaha sanayi atıksularından organik madde ve nutrientlerin giderilmesi amacıyla anaerobik batık membran biyoreaktör (AnSMBR) sisteminin kullanımı incelenmiştir. KOI, katı madde, alkalinite, uçucu yağ asitleri (UYA), yağ –gres, toplam azot (TN) ve fosfor (TP) gibi arıtma parametreleri periyodik olarak ölçülmüştür. Çıkış suyunda KOI 250-400 mg/L aralığında olmak üzere, %95 oranında giderim verimi belirlenmiştir. Reaktör girişinde UYA, 200-300 (HoAc/l) iken, çıkışta 120-160 (HoAc/l) olarak belirlenmiştir. TN ve TP giriş değerleri sırasıyla, 300 mg/l ve 45 mg/l iken, sistem çıkışında sırasıyla 240 mg/l ve 15 mg/l değerlerine indirgenmiştir. Besleme suyunda 1000 mg/L olan yağ-gres miktarı, %90 giderim verimi ile çıkış suyunda 45 mg/l değerine düşmüştür. Analiz sonuçları mezbaha atıksularının arıtılmasında, anaerobik batık membran biyoreaktör sisteminin yüksek oranda giderim verimleri sağladığını göstermiştir.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Anaerobic submerged membrane bioreactor; Treatment performance and removal efficiency; Flux; Trans-membrane pressure; Slaughterhouse wastewater industry; Anaerobik batık membran biyoreaktör; Arıtma performansı ve giderim verimi; Akı; Trans-membran basıncı; Mezbaha atıksuyu